The Influence of Pretreatment on Humic Acid Yield and 14 C Age of Carex Peat - Cook, G. T.; Dugmore, A. J.; Shore, J. S. (Radiocarbon, 1997)
The object of the study was to assess the effects of a range of pretreatment/extraction schemes on the yields of humic acid and humin obtained from peat and the subsequent radiocarbon ages. We analyzed peat from Flókadalur in northern Iceland, collecting material from a profile containing seven visible tephra horizons in the upper 3 m, whose form and extent indicated little disturbance to the section over the last 4000 yr. The results of a range of pretreatments demonstrated that time rather than the strength of alkali is the more important factor governing the extraction of humic acid. An increase in alkali molarity did not correspond to any systematic increase in yield, whereas an increase in time did, implying that the extraction is kinetically controlled. We found no evidence of variability in 14 C age due to pretreatment scheme or between different geochemical fractions of the peat. Further implications from this study are that bog stability and ecological simplicity produce a favorable environment for 14 C dating.